2003
DOI: 10.1111/1471-0366.00057
|View full text |Cite
|
Sign up to set email alerts
|

Plantation Slavery and Economic Development in the Antebellum Southern United States

Abstract: The relationship of plantation slavery in the Americas to economic and social development in the regions it was dominant has long been a subject of scholarly debate. The existing literature is divided into two broad interpretive models -'planter capitalism ' (Fogel and Engerman, Fleisig) and the 'pre-bourgeois civilization' (Genovese, Moreno-Fraginals). While each grasps aspects of plantation slavery's dynamics, neither provides a consistent and coherent historical or theoretical account of slavery's impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Plantation economies in general, and the tea sector in particular, have historically been associated with bondage and indentured labour systems, implying varying degrees of unfreedom for labourers (Raman 2010;Brass and Bernstein 1992;Post 2003). Notwithstanding the re-organization of the sector in response to changing market conditions and state intervention, there seems to be limited mobility of tea garden workers or their descendants in terms of diversification of sources of earnings and employment.…”
Section: Discussionmentioning
confidence: 99%
“…Plantation economies in general, and the tea sector in particular, have historically been associated with bondage and indentured labour systems, implying varying degrees of unfreedom for labourers (Raman 2010;Brass and Bernstein 1992;Post 2003). Notwithstanding the re-organization of the sector in response to changing market conditions and state intervention, there seems to be limited mobility of tea garden workers or their descendants in terms of diversification of sources of earnings and employment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the mid‐1800s US industrial segments of capital did not form a coalition with the powerful southern planters (who produced cotton) because while the former promoted trade barriers, the latter favoured free trade (Moore 1967). And, Post (2003, 327) adds that northern industrial capitalism and southern plantation slavery had ‘contradictory social requirements’ that hindered a North–South coalition (on this point, see also Moore 1967). Instead, class coalitions often cut across national boundaries.…”
Section: Creating Free Trade Under British Hegemony 1860–1914mentioning
confidence: 99%
“…These included a monocultural plantation system, slave labor, transportation networks, credit mechanisms, and associated economic interdependencies (e.g., Breen, 1985;Kulikoff, 1988;Post, 2003;Clark, 2006: 17-19). In fact, it has been observed that White ethnogenesis, at least in the colonial Chesapeake, evolved as part of a capitalist socioeconomic system based largely on tobacco cultivation (Bell, 2005).…”
Section: Tobacco Use and Ethnicitymentioning
confidence: 99%